Psychological Counseling with Internet-Addicted Youth. - Kaminska, Olga V. (Psychological Prospects Journal, 2017)
This article analyzes the specifics of psychological counseling of young people that show signs of Internet addiction. The author described the methodological principles of this kind of addiction, the influence over the youth, the strategies in correction the Internet addiction. The author found out that the Internet addiction should be viewed as a process of influence on personality by means of prevention, remedial and developmental tools to update its internal resources corresponding the changes in motivational value, emotional and volitional, cognitive areas, providing constructive perception of virtual reality. The article focuses on the specifics of the process of counseling as a mean of correcting the addictive behavior. The theoretical approaches and psychological trends underlying the development strategy of psychological counseling that deal with Internet-dependent people have been attached. The author described the basic stages of counseling, the problem that are solved at each stage of individual counseling. The expediency of using the method of motivational interviewing, which was included in the process of individual counseling and used to provide the sustained motivation overcome the internet addiction has been proved. Its use implies the emergence of changes in destructive behavior, which was a source of motivation of a dependent personality, who began to clearly understand the need for change.The process and the result of testing strategies developed the psychological counseling. During the test of the proposed strategy effectiveness the author has established the presence of structural changes that indicate a decline in Internet addiction of individuals who formed the experimental group, and that the process of counseling was held on the proposed scheme. Key words: internet addiction, addiction, psychological counseling, psychological counseling technique, psychological correction.